2020
DOI: 10.33899/ijvs.2019.126047.1216
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of the trunk and paw pad skin of the African palm squirrel (Epixerus ebii)

Abstract: The study was initiated to contribute to the meager knowledge of the anatomy of the African palm squirrel. Skin of the trunk and paw pads was the subject of interest. Basic gross and histological techniques were employed. The dorsal fur was grey with golden brown free endings, while the ventral fur was greyish white. The fur covered the entire trunk, extended through the dorsal surface of the distal carpal joint to the dorsal surface of the digits. Five digital pads, three inter-digital pads and two metacarpal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In digitigrade animals, which rest on the fingers, such as dogs and cats, digital and metacarpal (metatarsal) pads are also present and are the only pads that make contact with the ground, despite having carpal and tarsal pads, in the palmar and plantar regions, respectively (Dyce et al, 2010; Konig & Liebich, 2016). Other wild species have, in addition to finger pads, interdigital pads, associated with metacarpals and metatarsals, as reported by Ibe et al (2020) for the species Epixerus ebii , the african palm squirrel.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In digitigrade animals, which rest on the fingers, such as dogs and cats, digital and metacarpal (metatarsal) pads are also present and are the only pads that make contact with the ground, despite having carpal and tarsal pads, in the palmar and plantar regions, respectively (Dyce et al, 2010; Konig & Liebich, 2016). Other wild species have, in addition to finger pads, interdigital pads, associated with metacarpals and metatarsals, as reported by Ibe et al (2020) for the species Epixerus ebii , the african palm squirrel.…”
Section: Discussionmentioning
confidence: 57%
“…Eccrine sweat glands can assume different dispositions between species. Ibe et al (2020) observed several groups of these glands in the regions of the dermis and also in the hypodermis of Epixerus ebii , which act on the friction of the paw pads, with its location in an adipose medium attributed to its metabolic function for the production of vitamin D and triglycerides. Myrmecophaga tridactyla , the giant anteater, also presented well‐defined groups of glandular acini (atrial glands) in the dermis, as well as tissue arrangement similar to the studied Xenarthra's (Ribeiro et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The squirrel is found across Africa, south of the Sahara and savannah countries, usually around cultivated lands (Thorington et al, 2012). It is well distributed in Nigeria particularly in North-eastern and South-eastern parts of the country (Ibe et al, 2020). Six subspecies are currently recognized, two of which are in Nigeria; Xerus erythropus erythropus and Xerus erythropus chadensis (Herron & Waterman, 2004).…”
Section: Introductionmentioning
confidence: 99%